PENDEKATAN SISTEM ETIK DALAM PENGAMBILAN KEPUTUSAN MENGENAI TINDAKAN ABORSI - Ahmad Basuki (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
A process is applied to compile complex infirmation, values and interests that compete to one another to justify a particular ethical decision on abortion measures. In this case there are three standpoints namely conservative, liberal and democrat. Approach of ethical system in decision making on abortion measures that a fetus is an initial indication of a person’s life. Therefore, its growth and development must be respected both in view of its biological and social facets.